Implementasi Pelindungan Data Pribadi dalam Sistem Informasi pada Perusahaan Jasa Keuangan - Wyanda Kinanti Syauqi Ramadhani; Sidi Ahyar Wiraguna (Perspektif Administrasi Publik dan hukum, 2025)
The implementation of personal data protection in information systems at financial services companies is an important issue in this digital era. This study aims to analyze the implementation of personal data protection in information systems at financial services companies in Indonesia after the enactment of Law Number 27 of 2022 concerning Personal Data Protection (UU PDP). The main focus of the study is to identify the level of company compliance with the principles of personal data protection, the challenges faced in its implementation, and the legal and business implications that arise. The research method used is normative law with a qualitative approach, supported by literature studies and analysis of related documents. The results of the study show that although the PDP Law has been enacted, the implementation of personal data protection in the information systems of financial services companies still faces various challenges, including system complexity, varying stakeholder awareness, and the need for significant technology investment. This study concludes that more comprehensive efforts are needed from all relevant parties to ensure the effective implementation of the PDP Law and provide concrete suggestions for future improvements.